Beyond borderline : true stories of recovery from borderline personality disorder - Gunderson, John G., 1942-2019-; Hoffman, Perry D., 1944- (New Harbinger Publications, Inc., 2016)
This provocative book uncovers the truth about a misunderstood and stigmatized disorder, and offers an opportunity for a deeper, more empathetic understanding of BPD from the real experts and the individuals living with it.